Using straw bale in the construction of small units in informal settlements - Hamed, Amr Abd-El-Aty (AUC Knowledge Fountain, 2014)
An estimate of more than twelve million people are living in Egypt's congested growing informal settlements (slums). Characterized by the sever lack of social security, lack of basic services and high poverty rates indicates only the brighter picture of safe settlements. The scene however gets darker in second degree unsafe areas, with around 600,000 resident, the habitants of these areas are at grave risk, with their homes built with waste material that render the units unsafe for human habitation. With the government already falling behind all plans set to intervene, and develop or reallocate the existing areas; the rise of new unsafe areas will only make the picture worse. Moreover, habitants of agricultural lands informally build their homes using common building material, and on the other hand, the abundant rice straw produced from these lands are burned. The gravity of the problem requires developing an alternative feasible, safe and economical construction approach to limit unsafe informal areas. Straw bale (stacked bales of rice straw) has not been yet introduced as a structural element in the Egyptian construction market. Rice straw is an agricultural waste with around four million tons produced annually in Egypt, where 80% are burned resembling 50% of the factors causing the 'black cloud' phenomenon. The black cloud constitutes around 45% of Egypt's air pollution in the rice harvesting season, causing around 5000 deaths every year in addition to premature death, eye infections and chronic chest diseases such as pneumonia, chronic bronchitis and asthma attacks. The objective of this work is to study the applicability of using straw bale as structural bearing walls, in the construction of safe small units in informal settlements, thus limiting the rise of new unsafe areas of second risk, and informal areas on agricultural lands. To meet that objective, the physical and thermal properties of rice straw were examined. Tests including size variation, density, relative density, absorption, compressive strength, and fire proofing performance were also conducted for un-plastered and plastered bales. The structural bale construction method was also used to build a small residential unit model to investigate the feasibility and practicality of this approach. The results of this study investigation reveal that straw bale can be considered as a feasible, and safe construction option for small units in informal settlements. The feasibility of such approach is significantly better for settlements in the vicinity of agricultural land. The tests has shown that the variation in density of straw bale directly affects its stiffness and performance, meanwhile, the performance of plastered bales was not affected by the straw density. The moisture content and pH values of rice straw were within the acceptable range, allowing its safe use for construction applications. Rice straw has demonstrated an excellent thermal conductivity classifying it as a thermal insulating material. When preloaded, straw bale have witnessed a great increase in its stiffness. Cement rendering straw bale showed a significant enhancement in the absorption percentage, compressive strength, and fire proofing performance of the bale. Decreasing the plaster application quality of the bales has shown to reduce its compressive strength, and fire proofing performance. Using vertical re-bar supports and metal mesh lath seemed to enhance the straw bale wall performance, and the render strength respectively. When compared to common building techniques, the model constructed by the straw structural bale method has witnessed a significant cost saving. The mean estimate for the environmental and health degradation cost resulting from burning rice straw was around L.E 4.8 Billion in 2012. Further research works as well as pilot trials need to be conducted, to explore the full potential of straw bale and its applicability in construction.